PERENCANAAN STRATEGIS SISTEM INFORMASI DAN TEKNOLOGI INFORMASI STIKES PALEMBANG - Rudiansyah, Rudiansyah (Universitas Muhammadiyah Palembang, 2019)
The purpose of this study resulted in strategic planning of information systems and information technology. STIKES 'Aisyiyah palembang as one private health university in south sumatera is still having difficulty in determining the priority scale of SI / IT development. Therefore it is needed an information system planning and information technology with qualitative approach using ward and peppard framework. In analyzing the internal business environment the researcher uses the value chain method to map the main activities and supporting activities, the main activity of STIKES 'Aisyiyah Palembang is described using Business Process Modeling Notation (BPMN). the current external business conditions use the five forces model and for internal and external environment analysis SI / TI uses current technology trends. Based on internal and external business and SI / IT environment analyzes then formulated the future SI / IT strategy using SWOT analysis then determine the portfolio of upcoming applications using Mc. farlan strategic grid. Keywords: Strategic planning of ward and peppard, Business process, BPMN, application portfolio